Synthesis, Antitumor Activity, 3d-Qsar and Molecular Docking Studies of New Iodinated 4-(3h)-Quinazolinones 3n-Substituted - Castro-Alvarez, A; Castro-Alvarez, A (Royal Society of Chemistry, 2022)
A novel series of 6-iodo-2-methylquinazolin-4-(3H)-one derivatives, 3a-n, were synthesized and evaluated for their in vitro cytotoxic activity. Compounds 3a, 3b, 3d, 3e, and 3h showed remarkable cytotoxic activity on specific human cancer cell lines when compared to the anti-cancer drug, paclitaxel. Compound 3a was found to be particularly effective on promyelocytic leukaemia HL60 and non-Hodgkin lymphoma U937, with IC50 values of 21 and 30 μM, respectively. Compound 3d showed significant activity against cervical cancer HeLa (IC50 = 10 μM). The compounds 3e and 3h were strongly active against glioblastoma multiform tumour T98G, with IC50 values of 12 and 22 μM, respectively. These five compounds showed an interesting cytotoxic activity on four human cancer cell types of high incidence. The molecular docking results reveal a good correlation between experimental activity and calculated binding affinity on dihydrofolate reductase (DHFR). Docking studies proved 3d as the most potent compound. In addition, the three-dimensional quantitative structure-activity relationship (3D-QSAR) analysis exhibited activities that may indicate the existence of electron-withdrawing and lipophilic groups at the para-position of the phenyl ring and hydrophobic interactions of the quinazolinic ring in the DHFR active site. © 2022 The Royal Society of Chemistry.